І. Y. Golovash: TYPOLOGICAL FEATURE OF THE COGNITIVE-HEURISTIC MODEL OF ENGLISH VERB-CASUATIVE PATTERNS TRANSLATION INTO UKRAINIAN. - Golovash, І. Y. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
The article explores the possibilities of translating English causative constructions into Ukrainian within the framework of the cognitive-heuristic approach to translation. The authors analyze the concepts of causality, causal situation, the term “causative construction” and the structure thereof. The concept of the causative verb is discussed and different kinds of causative verbs are identified. The paper presents a critical analysis of the traditional approach to the problem of translating causative constructions within the framework of the linguistic theory of translation and identifies the limitations of the approach. At the next stage, the cognitive- heuristic model of translation is described and its three main component parts explored, including the cognitive search, concept recombination and the search for the translation language means of verbalizing meaning with auto-correction. Using the psycholinguistic method of introspection and examples from English texts containing various causative constructions, the author vividly demonstrates the possibilities of using the three kinds of mental operations discussed above in the solution of translation problems at different stages of the translation process. Special attention is paid to the role of the cognitive context. The paper identifies the most interesting regularities observed in the translation of English causative constructions into Ukrainian, among them the change of the causal image scheme into an action-consequence scheme and the possibility of verbalizing causal action and its consequence by means of one lexical unit. The general conclusion is made that by using all the three mental operations along with a monolingual dictionary of the English language and drawing on various kinds of knowledge including first of all background knowledge and the knowledge of context one can successfully translate causative constructions of different kinds in the cognitive context.